Feasibility of Skipjack Katsuwonus Pelamis Fishing Unit Business in the Flores Sea - Carda, Muhammad Aldair Mukstofa; Sugianto, Nur Islah; Nursanti, Nursanti (Newinera Publisher, 2025)
The present research determines the financial practicality of skipjack tuna (Katsuwonus pelamis) fishing unit establishments located in the Flores Sea portion of South Sulawesi. A survey-based research project took place between September and December 2024 to obtain data from Bulukumba and the Selayar Islands regencies through random sampling procedures. The research relied on interview sessions together with questionnaires and observations as well as literature review for data collection. The financial assessment performed a cost breakdown followed by income evaluation using NPV with IRR and Net B/C and PP calculations. The skipjack tuna fishing businesses employing purse seine gear in the Flores Sea operate at a profitable level. Financial analysis demonstrates profitability and sustainability potential because the regencies achieved positive NPV and IRR exceeding interest rates together with Net B/C Ratio values higher than one and PP that lasts for less than three years. The research results validate ongoing support for the skipjack tuna fishing industry throughout the region.